Impact of Priming in Varying Potassium Nitrate Concentrations and Durations on Germination of Two Barley Varieties (Hordeum vulgare L.) - Abusif Sonousi; Bilkess M. A. Salim; Abu baker A .M. Grein; Huda S. alrawig; Sherin M. A. Salim; Hajer M. Adam (African Journal of Advanced Pure and Applied Sciences, 2025)
Seed priming is a useful treatment that is done before sowing to help seeds germinate and grow quickly in many crops. This study in the Botany Department’s lab at Sebha University in Libya looked at 14 priming treatments in a completely random design (with three replicates) on two types of barley (Rehan and AboToreen). We measured the following traits: the percentage of seeds that germinated the germination index, the germination energy, the average time it took for seeds to germinate, the vigor of the seedlings, the length of the seedlings, and the fresh and dry weights of ten seedlings. Most traits showed big differences between treatments. The longest mean root length came from water priming for 6 hours, and the longest shoot length came from potassium nitrate (KNO₃) 5% for 12 hours. Fresh weight and vigor were optimized at certain duration–concentration combinations, demonstrating that both factors significantly influence barley germination and initial growth. Overall, the right priming solutions and exposure times can speed up emergence, boost vigor, and increase early biomass in barley. Simple water priming and 5% KNO₃ are two of the best choices for root and shoot growth, respectively.